Chinese State Capitalism and the Transition to Digital Television in Africa - Abikanlu, Femi (Television in Africa in the Digital Age, 2021)
The transition to digital television referred to as the Digital Switchover (DSO) process or Digital Migration is an agreement of member countries of the International Telecommunications Union (ITU) at the Geneva Conference in 2006. The agreement requires changes to national spectrum allocation and redeﬁnes national participation in the global digital television and mobile telephony market. While the decision of most African states to embark on the digital migration programme remains independent, the policies and approach to the implementation were inﬂuenced by two dominant economic orthodoxies, the neoliberal free market (Becchio and Leghissa 2016; Johnson 2011; Overbeek and Apeldoorn 2012; Peters 2011) which promotes a media environment mainly driven by market imperatives and the Chinese State capitalism (Bremmer 2008; Gu et al. 2016; Lyons 2007; Szamosszegi and Kyle 2011; Xing and Shaw 2013) which is the economic ideology that drives the interventions of the Chinese government in the region’s digital migration.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Identités diasporiques; Chine (corpus analysé); Nigéria (corpus analysé); Nouvelle-Zélande/Aotearoa (lieu de production du savoir); _Nettoyé

The Decolonial Turn in Media Studies in Africa and the Global South - Moyo, Last (Palgrave Macmillan, 2020)
This book develops a nuanced decolonial critique that calls for the decolonization of media and communication studies in Africa and the Global South. Last Moyo argues that the academic project in African Media Studies and other non-Western regions continues to be shaped by Western modernity’s histories of imperialism, colonialism, and the ideologies of Eurocentrism and neoliberalism. While Africa and the Global South dismantled the physical empire of colonialism after independence, the metaphysical empire of epistemic and academic colonialism is still intact and entrenched in the postcolonial university’s academic programmes like media and communication studies. To address these problems, Moyo argues for the development of a Southern theory that is not only premised on the decolonization imperative, but also informed by the cultures, geographies, and histories of the Global South. The author recasts media studies within a radical cultural and epistemic turn that locates future projects of theory building within a decolonial multiculturalism that is informed by trans-cultural and trans- epistemic dialogue between Southern and Northern epistemologies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; _Nettoyé